ChemInform Abstract: Perchloric Acid‐Functionalized Silica Nanosphere as Novel and Green Catalyst for the Synthesis of 2H‐Indazolo[2, 1‐b]phthalazinetrione Derivatives. Issue 52 (10th December 2015) - Chegeni, Mahdieh; Khazaei, Ardeshir; Rahmati, Sadegh; Fekri, Mohammad Hossein
Abstract: via multicomponent reaction of phthalhydrazide (I) with dimedone and aldehydes under solvent‐free conditions (14 examples)